Integrating Aboriginal and Torres Strait Islander Health Across an Undergraduate Medical Curriculum in Australia - Janie D Smith; Shannon A Springer (Bond University, 2017)
Introduction Many Australian university medical schools have struggled over the past decade to implement the professional standards and guidelines in Aboriginal and Torres Strait Islander health into their already crowded curricula. Bond University was no exception - with good intent but mixed results. In 2012 Bond renewed it medical program curricula and developed an innovative Aboriginal and Torres Strait Islander health education program, which is experiencing great success. Methodology The methodology included: establishing an Aboriginal and Torres Strait Islander health group (n=9); undertaking an extensive mapping process of the learning outcomes (n=63) from the standards and guidelines set by the profession; fleshing out the content which was allocated to years, semesters, and cases; developing an innovative implementation process based on a set of principles, and using structured program evaluation and a 5 year longitudinal study to measure the impact. Results Bond are now in their fifth year of implementing the Aboriginal and Torres Strait Islander health education with an innovative program that includes cultural immersion in the first year, problem based learning through identified cases, innovative processes for teaching difficult issues such as racism, as well as a structured assessment processes. Conclusion Aboriginal and Torres Strait Islander health is a well-integrated and accepted part of the normal medical curriculum and assessment process. Employing the right people, undertaking the extensive mapping process, having a documented implementation plan that all staff and students understood and accepted, based on the standards and guidelines of the profession, supported by strong leadership was critical for success.